Photothermal Lithography for Realizing a Stretchable Multilayer Electronic Circuit Using a Laser - Song, Sangmin; Hyejun Hong; Kim, Kyung Yeun; Kim, Kyun Kyu; Kim, Jaewoo; Won, Daeyeon; so young Yun; Choi, Joonhwa; Ryu Young In; Lee, Kyungwoo; Park Jae ho; Kang, Joohyuk; et al. (American Chemical Society, 2023)
Photolithography is a well-established fabrication method for realizing multilayer electronic circuits. However, it is challenging to adopt photolithography to fabricate intrinsically stretchable multilayer electronic circuits fully composed of an elastomeric matrix, due to the opacity of thick stretchable nanocomposite conductors. Here, we present photothermal lithography that can pattern elastomeric conductors and via holes using pulsed lasers. The photothermal-patterned stretchable nanocomposite conductor exhibits 3 times higher conductivity (5940 S cm？1) and 5 orders of magnitude lower resistance change (R/R0 = 40) under a 30% strained 5000th cyclic stretch, compared to those of a screen-printed conductor, based on the percolation network formed by spatial heating of the laser. In addition, a 50 μm sized stretchable via holes can be patterned on the passivation without material ablation and electrical degradation of the bottom conductor. By repeatedly patterning the conductor and via holes, highly conductive and durable multilayer circuits can be stacked with layer-by-layer material integration. Finally, a stretchable wireless pressure sensor and passive matrix LED array are demonstrated, thus showing the potential for a stretchable multilayer electronic circuit with durability, high density, and multifunctionality.